Stress response recruits the hippocampal endocannabinoid system for the modulation of fear memory - De Oliveira Alvares, Lucaa (2010)
The modulation of memory processes is one of the several functions of the endocannabinoid system (ECS) in the brain, with CB1 receptors highly expressed in areas such as the dorsal hippocampus. Experimental evidence suggested an important role of the ECS in aversively motivated memories. Similarly, glucocorticoids released in response to stress exposure also modulates memory formation, and both stress and dexamethasone activate the ECS. Here, we investigate the interaction between the ECS and glucocorticoids in the hippocampus in the modulation of fear memory consolidation. Two protocols with different shock intensities were used in order to control the level of aversiveness. Local infusion of AM251 into the hippocampus immediately after training was amnestic in the strong, but not in the weak protocol. Moreover, AM251 was amnestic in animals stressed 0, but not 30-min prior to the weak protocol, reverting the stress-induced facilitatory effect. Finally, intrahippocampal AM251 infusion reduced memory in animals that received dexamethasone immediately, but not 30 min before training. These results are (1) consistent with the view that the dorsal hippocampus ECS is activated on demand, in a rapid and short-lived fashion in order to modulate the consolidation of an aversive memory, and (2) show that this recruitment seems to be mediated by glucocorticoids, either in the hippocampus or in other brain regions functionally associated with the hippocampus. © 2010 Cold Spring Harbor Laboratory Press.